Socio-economic factors determining conservation and cultivation of Garcinia kola Heckel - a medicinal plant extinct in the wild in Benin - DADJO, Colombe; Nyende, Aggrey Bernard; SALAKO, Kolawolé Valère; Hounkpevi, Achille; ASSOGBADJO, ACHILLE EPHREM (My University, 2020)
Garcinia kola is a multipurpose tree and an important medicinal plant in most Western and Central African communities. The species is highly valued for its edible nuts and its different parts are used for the treatment of diverse ailments. Because of its overexploitation, G. kola is now extinct in the wild in Benin. Conservation and cultivation are crucial for its maintenance. Eliciting determinants that influence farmers’ decisions in maintaining or cultivating the species in their homestead or land would contribute to design effective management policies. A semi–structured survey was carried out with 155 respondents involved in G. kola exploitation to elucidate those determinants. Data collected were related to the socio–economic characteristics of respondents, G. kola ownership and number of individuals owned, current propagation methods and management of the species, willingness to cultivate or in situ conservation of the species. Binomial logistic and Poisson generalized linear models were used to test the effects of land area size, gender, age, and main occupation on respondents’ decision to cultivate and/or to conserve the species in situ and its management. It was found that men were more likely to own G. kola trees than women. Similarly, the likelihood of owning a G. kola tree was higher for farmers than non–farmers, and was positively correlated with respondents’ age. Furthermore, men were more willing to conserve and cultivate G. kola. Our findings suggest that the studied factors are instrumental when designing conservation policies and programs for the species.
Keywords: Conservation; Threatened species; Bitter kola; Sustainable management; Benin; Ethnobotany